Perbandingan Indeks Massa Tubuh Pasien Hipertiroid Praoperasi dan Pascaoperasi Tiroidektomi - Safitri, Yuliana; Setyawati, Martyarini Budi (Jurnal Penelitian Perawat Profesional, 2024)
Hyperthyroidism is a condition where the thyroid produces high amounts of TH and TSH hormones that affect the metabolic rate in the body. One of the clinical manifestations is weight loss as the calories produced are absorbed more quickly to produce energy. Thus patients with hyperthyroidism have a good appetite but weight gain is difficult or even weight loss occurs. The purpose of this study was to determine the comparison of preoperative and postoperative Body Mass Index of thyroidectomy in hyperthyroid patients. The research method used is the case study approach method, data obtained by observation for 3 months, namely from February 17, 2024 - May 17, 2024. Respondents in this study were Mrs. R with a medical diagnosis of hyperthyroidism who underwent thyroidectomy. The results of the study for 3 months showed a difference in preoperative Body Mass Index of 20.41 with postoperative Body Mass Index where there was a weight loss of 1 kg with a BMI value of 20.